The Influence of Work Facilities, Teamwork and Work Discipline on Employee Performance at the Pematangsiantar City DPRD Secretariat Office - Sinaga, Cristin Enjel; Sinaga, Anton A. P.; Panggabean, Toman (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effect of work facilities, teamwork and work discipline on employee performance at the Pematangsiantar DPRD Secretariat Office. The type of research used in this research is quantitative method. The sample in this study were employees at the Pematangsiantar City DPRD Secretariat Office as many as 35 people. The results showed that the work facility variable had a positive and significant effect on employee performance, with at value of 2.662> t table 2.039 and a sig value of 0.012 < 0.05, teamwork had a positive and significant effect on employee performance, with at value of 2.243> t table 2.039 and a sig value of 0.032 < 0.05, work discipline had a positive and significant effect on employees performance, with at value of 5.427> t table 2.039 and a sig value of 0.000 < 0.05. The results showed that work facilities, teamwork, and work discipline simultaneously had a positive and significant effect on employee performance, with a calculated F value of 29.462> F table 2.83 and a Sig value of 0.000